TINDAKAN KEPOLISIAN DALAM MENYELESAIKAN MASALAH PENJARAHAN/PENCURIAN DISAAT TERJADI SUATU BENCANA ALAM - Haerullah Nur Sidiq (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT            The theft by weight ever happened in Gulon Village. As explained above, theft during a natural disaster is classified as a criminal charge. This has been experienced by residents of Gulon Village. In 2010, an eruption of Mount Merapi occurred in Gulon Village, Salam District, Magelang District. This theft occurred for relief items intended for refugees. The relief items were taken at the refugee barracks located in Gulon Village Hall, Salam District, Magelang Regency. The theft occurred at night, 23.30 in 2010. The suspect entered the storage area of the goods, then the suspect took the relief items from the storage area without the knowledge of the goods manager. Every item that is issued must be in the knowledge of the goods registrar. Stolen relief items are a necessity for refugees, such as bed covers, rice plastic bags, milk the dancow, milk frisian, toothbrushes, flag tea, biscuits, indomie, chocolate milk, and others. Then put in a car to be taken to his house. Theft is the act of taking or stealing someone's property secretly with deception. Theft can also mean to take the property of others from the storage used. The goods are taken secretly and without the owner knowing.It can be concluded as follows: (1). For the police to provide security for the community is the responsibility of the profession. One of the main tasks of the police in the event of a crime is to conduct an investigation. The Investigation is a series of actions / forced efforts, examination, settlement, and submission of case files. In this case starting from the process of making police reports, investigations, summons, arrest, detention, search, confiscation, examination, filing, to the submission of case files and suspects and evidence (P-21), so that the actions Were taken by investigators / auxiliary investigators in every effort or step its actions can run effectively and efficiently in the context of law enforcement. (2). Efforts were taken by the police in overcoming theft committed during natural disasters in the Tassel Sector Police, First, preventive efforts in the form of all affairs or policies have taken long before the occurrence of an event in order to prevent the occurrence of theft crimes. Second, efforts curative is an action taken after the onset of a crime committed by someone with the aim that the crime or act of theft does not happen again. Third, Conduct coaching for the community. Keywords: theft by weight, natural disasters